2009
DOI: 10.1097/qad.0b013e32832f08a1
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of HIV, sexually transmitted infections, and associated high-risk behaviors among male clients of female sex workers in Tijuana, Mexico

Abstract: Objectives To determine sociodemographic and behavioral correlates of HIV infection among male clients of FSWs in Tijuana. Methods 400 men aged 18 or older who had paid or traded for sex with a FSW in Tijuana during the past 4 months were recruited in Tijuana’s “zone of tolerance,” where prostitution is practiced openly under a municipal permit system. Efforts were made to balance the sample between residents of the U.S. (San Diego County) and of Mexico (Tijuana). Participants underwent interviews and testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
104
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 28 publications
7
104
1
Order By: Relevance
“…In Belgium study there are also overlapping epidemics in men who have sex with men (MSM) where there are high number of HIV diagnose and incident STI [9]. Similar findings are reproduced in individualbased sectional studies including African American drug using women in USA on clients of female sex worker in Mexico [10,11]. Brainsttein and colleagues reviewed data of HIV incidence in subSaharan Africa 18 of 22 studies looking at impact of current or recent STI found an increased HIV risk, the highest HIV risk was found foeHSV2-seropositive [12].…”
Section: The Association Between Sti and Hiv Acquisitionsupporting
confidence: 64%
“…In Belgium study there are also overlapping epidemics in men who have sex with men (MSM) where there are high number of HIV diagnose and incident STI [9]. Similar findings are reproduced in individualbased sectional studies including African American drug using women in USA on clients of female sex worker in Mexico [10,11]. Brainsttein and colleagues reviewed data of HIV incidence in subSaharan Africa 18 of 22 studies looking at impact of current or recent STI found an increased HIV risk, the highest HIV risk was found foeHSV2-seropositive [12].…”
Section: The Association Between Sti and Hiv Acquisitionsupporting
confidence: 64%
“…62 Methamphetamine abuse has been linked to risky sexual behaviors in a variety of settings, 63 and has been associated with HIV/STI positivity and inconsistent condom use among FSWs and male clients in our previous research. 26,28,45,64 Our findings imply that the association between methamphetamine abuse and HIV/STIs may also hold true for FSWs' non-commercial male partners. Effective drug treatment options, including programs that focus on stimulant abuse and co-occurring conflict within relationships, are needed in these cities in addition to more comprehensive programs that recognize and address the co-occurrence of stimulant abuse, violence, and sexual risk among socially marginalized couples.…”
Section: Discussionmentioning
confidence: 81%
“…12 Nevertheless, we believe our findings underscore the need for continued prevention efforts targeting FSWs' male clients, who were found to have higher HIV prevalence than the non-commercial male partners in our sample (e.g., 4 % in Tijuana in 2008 vs. 1 % in our study). 45 We found that testing positive for HIV/STIs was associated with several individual and relationship factors. First, women who had regular sex work clients were less likely to test positive for HIV/STIs than women without regular clients.…”
Section: Discussionmentioning
confidence: 92%
“…In Mexico, prostitution is legal (Patterson et al 2009). Nevertheless, human trafficking and commercial sexual exploitation place undocumented, female migrant workers along the USAÁMexico border at the highest risk for HIV infection.…”
Section: Law Enforcement Of Sex Trade Industrymentioning
confidence: 97%
“…Nevertheless, human trafficking and commercial sexual exploitation place undocumented, female migrant workers along the USAÁMexico border at the highest risk for HIV infection. Estimates place the HIV prevalence rate as high as four per cent among male clients of female sex workers in Tijuana (Patterson et al 2009). Stricter law enforcement of the sex trade industry at border towns and crossing sites is warranted.…”
Section: Law Enforcement Of Sex Trade Industrymentioning
confidence: 98%